Showdown On The Energy Frontier. - Sandra Upson (IEEE spectrum)
Recent moves by the Moscow-based OAO Gazprom, the world's largest oil and gas company, have riled Western energy companies already working in Russia. Two situations in particular have brought issues to a head: one involves development of gas reserves around Sakhalin Island, just north of Japan, the other in an area in the Barents Sea near Murmansk known as Shtokman. Because of these fields' remote and hostile environments, Russia will need some of the most advanced technology in the world to exploit them. Major Western companies have shown interest but Russia is considering buying these technologies from other sources. Gazprom has already scrapped a bidding process that involved four prospective foreign partners, whose offers of stakes in other oil and gas projects had been deemed insufficient